2018
DOI: 10.1016/j.bbmt.2017.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Total Body Irradiation Is Safe and Similarly Effective as Chemotherapy-Only Conditioning in Autologous Stem Cell Transplantation for Mantle Cell Lymphoma

Abstract: Autologous stem cell transplant (ASCT) consolidation has become a standard approach for patients with mantle cell lymphoma (MCL), yet there is little consensus on the role of total body irradiation (TBI) as part of high-dose transplantation conditioning. We analyzed 75 consecutive patients with MCL who underwent ASCT at our institution between 2001 and 2011 with either TBI-based (n = 43) or carmustine, etoposide, cytarabine, melphalan (BEAM; n = 32) high-dose conditioning. Most patients (97%) had chemosensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In patients with follicular lymphoma secondary malignancies are obviously less frequent after BEAM than after TBI/cyclophosphamide. 44,45 The data of the Nordic Lymphoma Group suggest that the outcome of BEAM or BEAC is comparable with a TBI-containing protocol in MCL, 4 also the data of Tseng et al 46 In our cohort, we found a significantly lower OS after TBI compared to BEAM in the multivariate analysis. This observation should not be overestimated because of our small patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with follicular lymphoma secondary malignancies are obviously less frequent after BEAM than after TBI/cyclophosphamide. 44,45 The data of the Nordic Lymphoma Group suggest that the outcome of BEAM or BEAC is comparable with a TBI-containing protocol in MCL, 4 also the data of Tseng et al 46 In our cohort, we found a significantly lower OS after TBI compared to BEAM in the multivariate analysis. This observation should not be overestimated because of our small patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…According to the last European Society for Medical Oncology guideline, a rituximab containing induction of CHOP and cytarabine followed by ASCT and consolidation is recommended (7). ASCT consolidation is potentially curative and has become a standard approach for patients with MCL (10). Despite the high rate of complete response following systemic chemotherapy followed by ASCT, patients do relapse.…”
Section: Discussionmentioning
confidence: 99%